Peran Penyuluh Pertanian dalam Memanfaatan Kartu Tani untuk Meningkatan Produktivitas Petani Bawang Merah di Kecamatan Latimojong - Adelia Ikhwana; Anggra Alfian; Syafruddin Syafruddin (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Fertilizers play an essential role in increasing the productivity of shallot farmers in the Latimojong Regency. Still, the distribution of subsidized fertilizers is often not on time and not on target, thus hindering agricultural productivity. This gap shows the need to evaluate agricultural extension workers' use of farmer cards to increase shallot productivity in the Latimojong Regency. The research objectives are: 1). Analyzing the use of farmer cards in shallot farming activities. 2). analyzed the productivity of shallots in Latimojong District (3) analyzed the role of extension workers in shallot farming in Latimojong District; 4). Analyze the influence of the use of farmers and extension workers on productivity. This research was carried out in January-April 2024, and the data collection method included primary and secondary sources. The research sample amounted to 65 respondents who were taken deliberately (purposive) with the consideration of the highest onion producer in Luwu Regency who used the farmer card as a redeemer for subsidized fertilizer. The research sample was taken from 3 farmer groups. The variables in this study are the role of extension workers, the use of farmer cards, and productivity. Data analysis uses descriptive and inferential methods with a quantitative paradigm. Descriptive analysis explains the observed variables by creating categories based on the distribution of respondents. Meanwhile, inferential analysis uses the Variation-based Structural Equation Model (VB-SEM) to explain the influence between variables. The Smart PLS 3.92 and SPSS 25 software applications facilitate data analysis. The results of the study show that the use of farmer cards does not impact productivity growth. Even farmers experience difficulties in the flow of subsidized fertilizer collection. However, extension workers have a good impact on increasing shallot productivity.